Hepatotoxicity study of nanotitania on Mice and Zebra fish: A comparison. Issue 1 (December 2020) - Sharma, Vikash Kumar; Agrawal, Manoj Kumar
Abstract: The present paper for study aims the characterization and investigation of the oxidative stress induced toxicity of nanotitania in liver of mice and zebra fish models. Physical characterization for its size and the affirmation of phase by XRD, SEM, and TEM reveals, the particles as crystalline, predominant anatase phase with the mean size of about <50 nm. The toxic effect was assessed in vivo using the giant zebra fish 3-6 months old on two groups, viz, control and 24hr treated with 1ppm as experimental. Similarly 6-8 months old Mice with control and experimental groups (24 hour treatment of 50mg/kg bodyweight). Spectrophotometric analysis of the inductively coupled plasma optical emission confirmed the presence of nanoparticles in tissues. In both experimental models, a considerable raise in lipid peroxidation as well as liver marker enzymes ALT, AST and the decline within antioxidants such as SOD, Catalase, GPx due to TiO2 induced oxidant stress. Topographic evaluation of tissue through SEM reveals a remarkable uptake of nanotitania. Histopathological examination of TiO2 administrated groups infers cellular damage and DNA damage which was confirmed by COMET assay. It is substantial that nanoritania unlike to its bulk counterpart induces hepatotoxicity in both fish and Mice. The mice tissues are found to be more toxic than that of giant zebra fish in spite of better efficacy in its tissue.